Analisis Kontrol Aplikasi Untuk Menghasilkan Keakuratan Dalam Kelengkapan Informasi Pada Siklus Pendapatan Adorable Projects - Bobbyansyah Bobbyansyah; Elsje Kosasih (Universitas Kristen Maranatha, 2019)
Purpose - Application control is control in the company's business processes to prevent, detect, and correct transaction errors and irregularities. Application control will produce information needed by users so that the accuracy and completeness of information must be considered related to aspects of quality information. The purpose of application control is to ensure the accuracy and completeness of the information generated by the application system.Methodology - Descriptive study, this method compiled to collect data that describe the characteristics of a person, events, or situations. Data collections and research information were obtained from Adorable Projects as the object of research.Findings - The author drew the conclusions that the company's application control has not been fully adequate, that has caused that the production of information is not fully accurate and complete because there are several components has not implemented by the company. The Company only implemented 25 components from 31 components of application control. Although it is not fully adequate, the application control can still reduce risks in the application system.Value –Fully applying application control’s component on company business will provide accuracy and completeness of information that would be useful for increasing profit and competitive advantage on company’s revenue cycle. Keywords: Application Control, Revenue Cycle, Accuracy, Completeness